2022
DOI: 10.1186/s12933-022-01499-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phosphate and all-cause mortality in individuals with and without type 2 diabetes: the Dutch population-based lifelines cohort study

Abstract: Introduction Individuals with type 2 diabetes have a substantially elevated cardiovascular risk. A higher plasma phosphate level promotes vascular calcification, which may adversely affect outcomes in individuals with type 2 diabetes. We hypothesized that the association between plasma phosphate and all-cause mortality is stronger in individuals with type 2 diabetes, compared to those without diabetes. Methods We analysed the association between pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Recently it has been reported that high extracellular phosphate increases platelet polyP content [ 32 ]. Interestingly, emerging evidence indicates that phosphate metabolism is altered in diabetes [ 33 , 34 ]. Hyperphosphatemia has been described in an animal model of diabetes [ 35 ], and diabetes is considered a major risk factor for hyperphosphatemia through kidney disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been reported that high extracellular phosphate increases platelet polyP content [ 32 ]. Interestingly, emerging evidence indicates that phosphate metabolism is altered in diabetes [ 33 , 34 ]. Hyperphosphatemia has been described in an animal model of diabetes [ 35 ], and diabetes is considered a major risk factor for hyperphosphatemia through kidney disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%